Quantifying the environmental impact of a major coal mine project on the adjacent Great Barrier Reef ecosystems. (June 2022) - Saint-Amand, A.; Grech, A.; Choukroun, S.; Hanert, E.
Abstract: A major coal mine project in Queensland, Australia, is currently under review. It is planned to be located about 10 km away from the Great Barrier Reef World Heritage Area (GBRWHA). Sediment dispersal patterns and their impact on marine ecosystems have not been properly assessed yet. Here, we simulate the dispersal of different sediment types with a high-resolution ocean model, and derive their environmental footprint. We show that sediments finer than 32 μm could reach dense seagrass meadows and a dugong sanctuary within a few weeks. The intense tidal circulation leads to non-isotropic and long-distance sediment dispersal patterns along the coast. Our results suggest that the sediments released by this project will not be quickly mixed but rather be concentrated where the most valuable ecosystems are located. If accepted, this coal mine could therefore have a far-reaching impact on the GBRWHA and its iconic marine species. Highlights: We assessed the dispersal potential of sediments released from the CQC coal mine. Sediments finer than 32 μm could reach ecologically sensitive areas in a few weeks. Sediments follow non-isotropic and long-distance dispersal patterns. Sediments follow the western coastline of the bay, where seagrass meadows are found. Sediments can reach a dugong sanctuary and sea turtle nesting beaches.